2020
DOI: 10.1159/000511075
|View full text |Cite
|
Sign up to set email alerts
|

Doppler Activity and Ultrasonographic Detection of Intra-Abdominal Fistulas Are Predictors of Surgery in Crohn’s Disease

Abstract: <b><i>Bakground and Aim:</i></b> Predictors of the need for surgery in sticturing Crohn’s disease (SCD) are lacking. Bowel ultrasound (US) is a harmless, noninvasive, and inexpensive diagnostic procedure that has proven to be a valuable tool in the management of Crohn’s disease (CD). Our aim was to identify ultrasonographic findings in SCD that may associate with a higher risk of surgery, allowing us to make early choices regarding treatment election in this specific group of patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“… 31 Garcia et al reported that entero-enteric fistulas [ p = 0.04] and entero-mesenteric tracts [ p = 0.003], detected by IUS, were significantly associated with the need for surgery in the short term. 66 …”
Section: Resultsmentioning
confidence: 99%
“… 31 Garcia et al reported that entero-enteric fistulas [ p = 0.04] and entero-mesenteric tracts [ p = 0.003], detected by IUS, were significantly associated with the need for surgery in the short term. 66 …”
Section: Resultsmentioning
confidence: 99%
“…This can be defined as the need for medication escalation, use of corticosteroids, hospitalisation due to symptomatic disease, or major surgery for complications associated with CD. Pathological BWT and the presence of BWF have been associated with negative disease evolution, while the presence of at least one complication at baseline IUS increases the risk of surgery [7,19,28,53].…”
Section: Prediction Of Disease Evolution and Prognosismentioning
confidence: 99%